A PROPOSAL FOR A LEGISLATIVE CONFERENCE FOR U.S. UNIONS IN THE TOBACCO INDUSTRY (Tufts Archival Research Center, 2007)
Tobacco Institute (TI) proposal for a legislative conference for U. S. unions in the tobacco industry. Demonstrates need for "union solidarity in defense of industry jobs," and calls for more awareness and organization. Aims to increase the awareness of union staff and officials, educate labor unions as to the economic importance of tobacco, and coordinate unions. Proposes ideas for a convener, cosponsers, participants, the date, and the program.